Homoeroticism and orientalism: The 'oriental' men in Western ethno-pornographic photography, 1850s to 1900s - Hansen, Emil Theodor (Culture and History: Student Research Papers, 2025)
In the recent years, the field of Colonial Middle East has seen a great revision. Taking outset from Edward Said’s seminal work on ‘Orientalism’, this paper aims to explore the sexual – or rather the homoerotic – implications of this scholarly debate. By examining ethnographic photography depicting supposedly ‘Oriental’ men, I argue that the portrayals of these models – which are characterised by a feminine and highly sexualised modelling – emphasise the colonial implications of the ‘Westernised’ perspective on ‘the Orient’. The feminine portrayal of the ‘Oriental’ models mirrors the conception of a subaltern ‘Orient’ from the perspectives of the European consumers.